Subset-specific expression of toll-like receptors by bovine afferent lymph dendritic cells - Werling, Dirk; Hope, Jayne C.; Siddiqui, Nazneen; Widdison, Stephanie; Russell, Chris; Sopp, Paul; Coffey, Tracey J. (Frontiers, 2017)
Within the ruminant system, several possibilities exist to generate dendritic cells migrating out from the tissue into the regional draining lymph nodes as afferent lymph dendritic cells (ALDCs). Here, we analyzed toll-like receptor (TLR) 1–10 mRNA expression by using quantitative real-time PCR in highly purified subsets of bovine ALDC. As TLR expression may be influenced by pathogens or vaccines and their adjuvant, it is necessary to understand what TLRs are expressed in a steady-state system to elucidate specific differences and to potentially optimize targeted vaccines. In this study, we have assessed the TLR expression profiles of the four main bovine ALDC subsets [cDC1 and cDC2 (subsets 2–4)]. We demonstrate differences in TLR expression between the four subsets that may reflect the ability of these cells to respond to different pathogens or to respond to adjuvants.